Oppiid mites (Acari: Oribatida: Oppiidae) from Alborz Province, with a key to the known species and new records for Iran - Maryam Keshavarz Jamshidian; Mohammad Ali Akrami; Alireza Saboori (Persian Journal of Acarology)
In the course of a faunistic survey on oppiid mites in Alborz Province, 29 oppiid mite species (Oribatida: Oppiidae) belonging to 11 genera were identified from soil and litter samples, of which three species and one subspecies are new records for the mite fauna of Iran. For new species records, a brief diagnostic characterization is provided. A key to the subfamilies, genera and subgenera of Alborz Province is given. Moreover, a key to species for genera with more than one species is presented.